(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the development of military-patriotic qualities in the defense of the Motherland, its national security, territorial integrity and sovereignty, youth military culture and its specific features. The place and role of mechanisms of military culture in the formation of military culture competences in young people and their upbringing as morally and morally mature people have been researched, and socio-pedagogical issues of military culture have been revealed.